Haci Bektash Veli and Bektashism in Russian Sources - Beyler, Fegani (Journal of Alevism-Bektashism Studies, 2020)
Haci Bektash Veli (d. 1271[?]), considered to be the founder of the Bektashism, is one of the leading representatives of Turkish-Islamic thought and belief traditions. He is a person whose influence continues today, as in the past, not only in Anatolia, but also in many countries such as Azerbaijan, Iraq, Egypt, Bulgaria, Greece, Albania and even Hungary, both as historical personality and with his mythical aspects, and his teachings. Haci Bektash Veli and his influence in the entire Turkish-Islamic world, especially in Anatolia, have caught the attention of the researchers from the fields of History, Language, Literature, Sociology, etc. Since the first studies on Haci Bektash Veli and Bektashism have been revealed, many works have been written in this field in various societies. Moreover, these studies become an independent research area over time. In particular, orientalists, including many turkologists, historians, philologists and experts in Islamic studies, were involved in this field, wondering about Turkish-Islamic world. In other words, many researches about Haci Bektash Veli and Bektashism have been carried out both in our country and abroad; original works and translations, such as articles, encyclopaedia articles, monographs, journal special issues, tribute books, surveys and publications, annuals, bibliographic studies, etc. were published in this field. These studies also found their own expression in the scientific events, such as special national and international congresses, symposiums and conferences. Russian-Soviet researchers, who mostly include turkologists, historians, philologists, ethnologists and experts in Islamic historical researches and have a large expert staff, have focused on the great role and effects of Haci Bektash Veli in the preservation of Turkish-Islamic thought and culture. Correspondingly, the essence and philosophical foundations of Bektashism have also attracted their attention. As a result of this process, that began with curiosity and turned into academic interest, a significant literature in Russian on Haci Bektash Veli and Bektashism has emerged. The aim of this paper is to identify- within the available possibilities- Russian written sources on Haci Bektash Veli and Bektashism, to reveal the prominent studies among them and to present comments and evaluations of Russian researchers and other authors who have written their academic publications in Russian in this field, by using the method of description and evaluation. We should specify that in the paper we followed a chronological order taking into account the dates on which these studies were conducted. Finally, this paper aims to contribute to the literature in Turkish on Haci Bektash Veli and Bektashism. Thus, the author of the paper hopes that the paper will be useful in terms of the directory of sources and materials for the ongoing and future researches in our country.